Penerapan Metode Adams-Bashforth-Moulton pada Persamaan Logistik Dalam Memprediksi Pertumbuhan Penduduk di Provinsi Kalimantan Timur - Apriani, Dewi; Wasono, Wasono; Huda, Moh. Nurul (EKSPONENSIAL, 2022)
Logistic equation is a nonlinear ordinary differential equation that describes the population. Nonlinear ordinary differential equations can be solved by one of the numerical methods, namely the Adams-Bashforth-Moulton method. Adams-Bashforth-Moulton method is a multistep method which consists of Adams-Bashforth method as predictor and Adams-Moulton method as corrector. The logistic equation is solved first by using the Runge-Kutta method to obtain the four initial solutions, then followed by the Adams-bashforth-Moulton method. This study aims to predict population growth in the province of East Kalimantan using the Adams-Bashforth-Moulton method. Based on the calculation results obtained a numerical solution of the logistic equation for population growth at , with a step size of , the capacity of the province of East Kalimantan is and the growth rate of is 3,856,564 inhabitants.